The short-term prognosis of very late onset generalized myasthenia gravis: a single-center retrospective cohort study - Liampas, Ioannis; Veltsista, Dimitra; Batzikosta, Paraskevi; Lazarou, Lefteris; Kefalopoulou, Zinovia Maria; Chroni, Elisabeth (Frontiers in Neurology, 2025)
ObjectiveTo explore the short-term prognosis of generalized very-late-onset myasthenia gravis (vloMG, symptom onset ≥65 years) in comparison with early- and late-onset MG (eloMG, <65 years).MethodsA single-center retrospective cohort study was conducted based on the medical records of patients with laboratory confirmed generalized MG, monitored in the specialized Unit of Neuromuscular Disorders of the University Hospital of Patras. Measures of clinical severity were compared at baseline and over the short term (2-year) follow-up.ResultsThere were 42 eligible patients (42.1 ± 13.2 years, 50% women, 19.5 ± 6.0 months follow-up) in the eloMG and 26 (72.4 ± 5.0, 50% women, 13.9 ± 7.9 months follow-up) in the vloMG group. In the vloMG group, AchR antibody positivity (89% vs. 57%, p = 0.007) and oculo-bulbar symptoms at onset (88% vs. 53%, p = 0.002) were more common, whereas thymus pathology (0% vs. 40%, p < 0.001) and generalized weakness at onset (12% vs. 38%, p = 0.018) were less frequent. Intubation within the first month from diagnosis was required only in patients with vloMG (5/26) (p = 0.006). Over the follow-up: the unadjusted incidence rate ratio (IRR) of relapses was lower in the vloMG group [IRR = 0.49, 95% CI = (0.26, 0.92), p = 0.026], the unadjusted odds (OR) of being classified as <IIb on the MGFA classification were higher in the vloMG group [OR = 2.27 95% CI = (1.02, 5.05), p = 0.043] and the average unadjusted difference in corticosteroid intake was lower in the vloMG group by approximately 6.9 mg [(−10.6, 3.3), p < 0.001] in equivalent doses of prednisolone [6.1 mg (−10.0, −2.2), p = 0.002, according to adjusted estimations].ConclusionDespite its more aggressive onset, vloMG has a more favorable prognosis than eloMG.